Drone UAV Pemadam Kebakaran Otomatis - Yusuf Arqam Nurkarim; Asslia Johar Latipah; Sayekti Harits Suryawan (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2020)
The high number of land areas damaged by forest fires in Indonesia is a problem that we often face. Handling that is difficult makes it difficult to extinguish quickly so that the forest fires become widespread. One solution to overcome this is to make an Automatic Forest Fire Fighting UAV Drone Robot so that it can quickly extinguish so that hotspots can be overcome before they become more widespread. The UAV drone itself is one of the multicopter flying vehicles that can be controlled manually and automatically, making it easier to reach points that cannot be reached by humans. By implanting a fire sensor, this tool is able to recognize fire points based on the infrared waves emitted by the fire. The Arduino microcontroller allows UAV drones to fly automatically to the point of fire based on the signal sent by the fire sensor. Using GPS as a directional guide so that the accuracy of the drone's flying direction is more accurate and can quickly release a fire extinguisher to extinguish the fire before it gets bigger.